Role of conservative management of genitourinary fistula: review of literature - Pal, Reena; Prasad, Deepmala Bhagwan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Regardless the etiology, the development of genitourinary fistula has the most profound and devastating consequences for patient’s physical and social life and remains a challenge to surgeons. Although the advancement has been made in the management but still the controversies are exist on the ideal time and approach. The spontaneous closure of vesicovaginal fistulae after continuous bladder drainage alone for varying periods has been reported in literature. This review was undertaken to look in to the literature regarding recent advancement in the conservative management of genitourinary fistula.